2018
DOI: 10.1186/s13104-018-3987-0
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women adherence level to antenatal care visit and its effect on perinatal outcome among mothers in Tigray Public Health institutions, 2017: cohort study

Abstract: ObjectiveTo assess pregnant women adherence level to antenatal care visit and its effect on perinatal outcome among mothers in Tigray Public Health institutions, 2017.ResultsThe overall adherence level of the women towards to antenatal care visit was 49.9% and incidence of PPH, still birth, early neonatal death, late neonatal death and low birth weight complication was 4.3%, 2.3%, 2.7%, 1.9% and 7.5% respectively. PPH, preterm labor, early neonatal death and LBW complication was reduced by 81.2%, 52%, 61% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
48
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 17 publications
(12 reference statements)
9
48
1
2
Order By: Relevance
“…The utilization of pregnancy care services is also varied based on mother 's age, mother's education, parity, mother's job, socio-economical status of family, residence, and access to health services. 31 In addition to variable of pregnancy care, this study also showed that variables of mother's age, parity, birth attendant, birth place, history of pregnancy complication in the previous pregnancy, history of birth complication in the previous labor, were associated with child birth complication Limitations of the study.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The utilization of pregnancy care services is also varied based on mother 's age, mother's education, parity, mother's job, socio-economical status of family, residence, and access to health services. 31 In addition to variable of pregnancy care, this study also showed that variables of mother's age, parity, birth attendant, birth place, history of pregnancy complication in the previous pregnancy, history of birth complication in the previous labor, were associated with child birth complication Limitations of the study.…”
Section: Resultsmentioning
confidence: 75%
“…Referens i that women who never attended prenatal care were more in preterm labors (OR 3.1, 95% CI 1.4-6.8), lower birth weight (P<0.001) and more given up for adoption (OR 21.4, 95% CI 2.63-173.9); Abera Haftu et al 31 conducted a study to assess pregnant women adherence level to antenatal care visit and its effect on perinatal outcome among mothers in Tigray Public Health institutions. The study showed that the overall adherence level of the women towards to antenatal care visit was 49.9% and incidence of PPH, still birth, early neonatal death, late neonatal death and low birth weight complication was 4.3%, 2.3%, 2.7%, 1.9% and 7.5% respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, SGD three (3) calls for the acceleration of current progress in order to achieve a global Maternal Mortality Ratio (MMR) of 70 maternal deaths per 100,000 live births in 2030. It was noted that this global MMR reduction and positive pregnancy can only be realized if the ANC provided to women during pregnancy improves and they seek early ANC services [7].…”
Section: Background Of the Studymentioning
confidence: 99%
“…Adequate and quality antenatal care (ANC) is effective at promoting better health outcomes for both the mother and child during pregnancy (1,2). Strong evidence exists to support the link between ANC during pregnancy, skilled birth attendant during delivery and quality postnatal and reduced maternal and infant morbidity and mortality (3)(4)(5)(6)(7)(8). Globally, almost 60% of stillbirths are due to poor fetal growth, untreated and unattended maternal infection and conditions, which could have been prevented or treated by expert attention available during ANC visits (7).…”
Section: Introductionmentioning
confidence: 99%